Investigating new treatment opportunities for patients with chronic kidney disease in type 2 diabetes: the role of finerenone. Issue 6 (6th December 2020) - Agarwal, Rajiv; Anker, Stefan D; Bakris, George; Filippatos, Gerasimos; Pitt, Bertram; Rossing, Peter; Ruilope, Luis; Gebel, Martin; Kolkhof, Peter; Nowack, Christina; Joseph, Amer; ,
Abstract: Despite the standard of care, patients with chronic kidney disease (CKD) and type 2 diabetes (T2D) progress to dialysis, are hospitalized for heart failure and die prematurely. Overactivation of the mineralocorticoid receptor (MR) causes inflammation and fibrosis that damages the kidney and heart. Finerenone, a nonsteroidal, selective MR antagonist, confers kidney and heart protection in both animal models and Phase II clinical studies; the effects on serum potassium and kidney function are minimal. Comprising the largest CKD outcomes program to date, FIDELIO-DKD (FInerenone in reducing kiDnEy faiLure and dIsease prOgression in Diabetic Kidney Disease) and FIGARO-DKD (FInerenone in reducinG cArdiovascular moRtality and mOrbidity in Diabetic Kidney Disease) are Phase III trials investigating the efficacy and safety of finerenone on kidney failure and cardiovascular outcomes from early to advanced CKD in T2D. By including echocardiograms and biomarkers, they extend our understanding of pathophysiology; by including quality of life measurements, they provide patient-centered outcomes; and by including understudied yet high-risk cardiorenal subpopulations, they have the potential to widen the scope of therapy in T2D with CKD. Trial registration number: FIDELIO-DKD (NCT02540993) and FIGARO-DKD (NCT02545049)